Answer:
[tex]Sum = 1.67[/tex]
Step-by-step explanation:
Given:
[tex]1.5x^2 - 2.5x -1.5 = 0[/tex]
Required
Determine the sum of the solutions
This question will be answered using quadratic formula:
[tex]x = \frac{-b\±\sqrt{b^2 - 4ac}}{2a}[/tex]
Where:
[tex]a = 1.5[/tex]
[tex]b = -2.5[/tex]
[tex]c = -1.5[/tex]
So, we have:
[tex]x = \frac{-(-2.5)\±\sqrt{(-2.5)^2 - 4*1.5*-1.5}}{2*1.5}[/tex]
[tex]x = \frac{2.5\±\sqrt{6.25 +9}}{3}[/tex]
[tex]x = \frac{2.5\±\sqrt{15.25}}{3}[/tex]
[tex]x = \frac{2.5\±3.91}{3}[/tex]
[tex]x = \frac{2.5+3.91}{3}[/tex] or [tex]x = \frac{2.5-3.91}{3}[/tex]
The sum of the solution is then calculated as:
[tex]Sum = \frac{2.5+3.91}{3} + \frac{2.5-3.91}{3}[/tex]
Take L.C.M
[tex]Sum = \frac{2.5+3.91+2.5-3.91}{3}[/tex]
[tex]Sum = \frac{5}{3}[/tex]
[tex]Sum = 1.67[/tex]